Invalidation and low-order model set for artificial pancreas robust control design. (April 2019) - Bianchi, Fernando D.; Moscoso-Vásquez, Marcela; Colmegna, Patricio; Sánchez-Peña, Ricardo S.
Highlights: Based on a low-order control-oriented model an LPV model-set is calculated. The LPV model set is computed by an (in)validation procedure. A robust switched-LPV controller based on this set and another one based on the nominal LPV model are designed. Simulations show that the robust controller can take care of different (dynamic, parametric) uncertainties, whereas the nominal controller cannot. Abstract: The purpose of this work is to compute a linear parameter-varying (LPV) model set that describes the insulin-glucose dynamics in type 1 diabetes (T1D). This set includes a nominal LPV model and dynamic uncertainty and is amenable to controller design. The nominal model is an LPV control-oriented model previously published by the authors that is (in)validated in this work against the UVA/Padova metabolic simulator. The result is a set of models that is used to design a switched LPV robust controller to account for nonlinearities and variations in insulin sensitivity ( S I ). Closed-loop responses obtained with the robust controller and a nominal one are compared. Results illustrate the convenience of including robust strategies in designing control laws for an artificial pancreas (AP).